2019
DOI: 10.1039/c9em00257j
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: mercury mobility and methylmercury formation in a contaminated agricultural flood plain: influence of flooding and manure addition

Abstract: We investigated the release of mercury from soil to soil solution and the formation of methylmercury in polluted agricultural floodplain fields during a flooding incubation experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 68 publications
3
32
0
Order By: Relevance
“…The direct impact of Hg on the earthworms' biomass might have been outweighed by the rich soil quality in experiment 1 and the poor quality in experiment 2. However, the accumulation of both THg and MeHg in the earthworms compared with in the soil matrix was considerable in both experiments, in line with observations from previous field studies of a correlation between Hg bioaccumulation and soil total Hg, organic matter and clay contents [23,27,48]. Furthermore, the Hg and MeHg bioaccumulation might have affected the earthworms over a longer period than the incubation duration, for example by impacting their burrowing behavior or respiration [49].…”
Section: Hg Contamination In Soils and Its Effect On Earthwormssupporting
confidence: 89%
See 3 more Smart Citations
“…The direct impact of Hg on the earthworms' biomass might have been outweighed by the rich soil quality in experiment 1 and the poor quality in experiment 2. However, the accumulation of both THg and MeHg in the earthworms compared with in the soil matrix was considerable in both experiments, in line with observations from previous field studies of a correlation between Hg bioaccumulation and soil total Hg, organic matter and clay contents [23,27,48]. Furthermore, the Hg and MeHg bioaccumulation might have affected the earthworms over a longer period than the incubation duration, for example by impacting their burrowing behavior or respiration [49].…”
Section: Hg Contamination In Soils and Its Effect On Earthwormssupporting
confidence: 89%
“…Two experiments were performed in 5-L polypropylene pots (19 cm in diameter) with perforated lids, where soil and earthworms were incubated. For both experiments, soils were collected (in October 2015 for experiment 1 and October 2016 for experiment 2) in a field near the town of Raron in Canton Valais, Switzerland (46 • 18 10.6" N, 7 • 48 34.2" E), where long-term severe Hg pollution had been reported [24,[26][27][28]. The pollution originated from sediments of a canal that received a large amount of Hg (estimated at 50 to 250 tons) from ca.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The release of Hg to the soil solution and its further transport has been associated with the mobilization of NOM (Kronberg et al, 2016;Eklöf et al, 2018;Åkerblom et al, 2008), copper (Cu) nanoparticles (Hofacker et al, 2013) or the reductive dissolution of Fe/Mn-oxyhydroxides (Frohne et al, 2012;Gygax et al, 2019;Poulin et al, 2016). Earlier studies reported an immediate decrease of dissolved Hg after its release upon flooding in various riparian settings (Hofacker et al, 2013;Poulin et al, 2016;Gygax et al, 2019). Possible pathways for this decrease are Hg 2+ reduction to Hg 0 , sorption to recalcitrant NOM, formation of meta-cinnabar ß-HgS(s) or co-precipitation of Hg in sulfides (e.g.…”
Section: Introductionmentioning
confidence: 99%